Mechanisms for Financing General Budget Deficit: A Comparative Study between Algeria and Sudan - Sefiane , Hanane; NOUI , Noureddine (Journal of Research in Finance and Accounting, 2021)
This study aims to shed light on the experience of Algeria and Sudan in attracting national savings and financing the public budget deficit. Algeria has amended the Loan and Cash Law 90/10 and promulgated Law No. 17-10 on non-conventional finance despite the risks involved. On the other hand, Sudan adopted the issuance of Islamic Sukuk, considering the absence of inflationary effects, and its importance in mobilizing savings from various sources and directing the financing of investments, in addition to financing projects in the public sector through providing the necessary funds for infrastructure projects and addressing the shortcomings of finance.